Understanding the role of long-chain polyunsaturated fatty acid and antioxidants in enhancing rooster semen quality: a comprehensive review - Sithole, Sindisiwe Mbali; Nephawe, Khathutshelo Agree; Mphaphathi, Masindi Lottus; Ngcobo, Jabulani Nkululeko (Frontiers in Animal Science, 2025)
A significant amount of long-chain polyunsaturated fatty acids, such as arachidonic acid (ARA) and docosatetraenoic acid (DHA) (C20:4n-6 and C22:4n-6, respectively), are present in rooster semen. The ARA is a form of omega-6 fatty acid with a vital part in several biological procedures such as cell membrane structure and sperm cell signaling pathways. The DHA is a major polyunsaturated, crucial for the rooster semen quality, thus linked to the male reproductive efficiency. Despite the DHA link to rooster semen quality and fertility, it has been found to undergo a serious decrease as roosters age. Moreover, the frozen-thawed rooster semen survival is still low, spurring innovative strategies to improve frozen-thawed rooster semen, sperm cell damage leading to the negative impact on motility, viability, and membrane integrity. These challenges sparked interest in using long-chain polyunsaturated fatty acids, particularly omega n-3 and omega n-6, to increase spermatozoa quality and reproductive efficiency. Noteworthy, chickens cannot synthesize omega n-3 and omega-n-6 de novo, necessitating their dietary supplementation. In rooster sperm, omega-6 polyunsaturated fatty acids are natural components that are vital for achieving an optimal fertility rate. However, the dietary supplementation of these long-chain polyunsaturated fatty acids alone has been reported to result in lipid peroxidation and sperm susceptibility to reactive oxygen species, necessitating the addition of a natural antioxidants. Although previous studies have shown that both fresh and preserved semen have improved semen parameters and a good fertility rate when antioxidants are supplemented to the diet, there have been conflicting results after adding antioxidants and long-chain polyunsaturated fatty acids (LCPUFAs) to the diet. Therefore, this review’s goal is to postulate the understanding of the role of LCPUFA precursors as antioxidants, their challenges, and perspectives on the improvement of rooster semen quality. Enhancing rooster semen quality supports better fertility and hatchability in poultry, contributing to sustainable food production systems and ensuring affordable protein sources for communities, thereby addressing Sustainable Development Goals (SDGs) particularly on zero hunger and food security.